THE CHALLANGES OF ACCOUNTABILITY AND TRANSPARENCY IN THE - THAKASO, REFILOE (My University, 2011)
The Civil Service inefficiency in the last two to three decades prompted governments and international development partners to put more emphasis on the reforms in an effort to improve accountability and transparency. Despite these efforts the civil service continue to be shrouded with practices that defy accountability and transparency and total disregard of economic and efficient use of public resources; and therefore ineffective in service delivery. The argument presented contends that the political and administrative deficiencies or shortfalls inherent within government have resulted in poor financial and administrative management of public resources. These have destroyed the professional and social fiber of political leaders and public officials to the extent that pubic demands are sidelined to pursue interests of certain individuals who hold positions of power. In the process management of programmes and the financial management are inefficient weakening accountability and transparency. Weak accountability and transparency mechanisms have been manifested in reports of inefficiency, corruption, waste and misuse of public resources and poor service delivery as reflected in AG’s reports, the media and parliamentary debates. There are also gaps in the auditing of annual accounts the Parliament and the Executive turned a blind eye on this, indicative of lack of commitment towards accountability and transparency. The research has revealed the following as challenges for effecting accountability and transparency mechanisms: Information flow on the activities of the executive from the ministries to Parliament is inadequate, inaccurate and not submitted on time. The information system within the ministries is weak as there is missing information and some not properly recorded making information necessary for accountability and transparency inadequate. This was a result of non-compliance with the financial rules and regulations and these compounded by the fact that the work was not properly supervised and well monitored. Noncompliance was also aggravated by the fact that the authorities gave directives for incurring certain expenditures which were in conflict with the stipulated rules and iii regulations and therefore weakening the system of information recording. Financial management system has loopholes which hinder information recording for transparency to be achieved. There were also weak internal controls which went unabated resulting in inadequate information on the use of public funds. Inherent skill deficit aggravated inefficiency hence weak accountability and transparency. OAG responsible for ensuring that Parliament gets information receives poor quality information due to inaccessibility and unavailability of some information making the information insufficient and inaccurate. This coupled with shortfalls within the office such as lack of independence impedes the office from obtaining the quality of staff and lacks other resources such as equipment and vehicles which are necessary for carrying out its mandate efficiently. Audit coverage is therefore about 20% of the government ministries and not all programmes are covered. Staff turnover due to uncompetitive government salary compounds the problem of staff as a result there is low audit coverage further constraining obtaining of quality information from the ministries. This results in parliament receiving information that is not credible to make an assessment of government performance adequately. The legislative scrutiny continues with the deficient information that it receives, and from the PAC hearings there has been evidence of officers not being able to give credible account of how the resources have been expended, and unconvincing justifications were given for financial mismanagement. This weakens the quality of analysis by the PAC and this coupled with the skill deficit within the PAC and lack of parliamentary research capacity hindering expert judgment aggravates the problem of legislative scrutiny and evaluation hence the quality of feedback to the ministries. The audit reports are also not well publicized as there are no public hearings and no press conferences when the audit report is issued. Civil Society that plays a role in making government accountable by questioning and scrutinising its actions was weak and lacked the muscle to put government to task for financial mismanagement. Moreover, the media though vibrant its coverage does not reach most parts of the country except the national iv radio station which is seen to be monolithic and biased in reporting on performance of government. The ministries did not attend to PAC recommendation appropriately and on time and while the legislature is empowered to enforce compliance however, the follow-up mechanisms were weak and it was incapable of eliciting response to PAC suggestions from the executive. The executive did not feel compelled to respond to the PAC recommendations hence were ignored. This rendered the legislative and oversight structures and systems inadequate, the public financial management system weak and in efficient and ineffective monitoring of the executive arm of government. The conclusion derived from this is that a negative attitude of political and bureaucratic leaders towards accountability weakens accountability and transparency. And unless there is sufficient high level commitment to robust accountability the PAC and OAG cannot succeed in obtaining credible information on accountability and the PAC and Civil Society cannot hold the executive accountable as this could only be achieved if government permits it to happen
MM - P&DM
Keywords: Accountability; Transparency; Lesotho; Civil Service, Lesotho